2010
DOI: 10.1103/physrevd.82.101701
|View full text |Cite
|
Sign up to set email alerts
|

Infrared propagators of Yang-Mills theory from perturbation theory

Abstract: We show that the correlation functions of ghosts and gluons for the pure Yang-Mills theory in Landau gauge can be accurately reproduced for all momenta by a one-loop calculation. The key point is to use a massive extension of the Faddeev-Popov action. The agreement with lattice simulation is excellent in d=4. The one-loop calculation also reproduces all the characteristic features of the lattice simulations in d=3 and naturally explains the pecularities of the propagators in d=2.Comment: 4 pages, 4 figures

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
312
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(344 citation statements)
references
References 31 publications
32
312
0
Order By: Relevance
“…We also demonstrate that, within perturbation theory, correlation functions of YM fields are identical to those obtained in a massive extension of the usual FP gauge-fixed action, which is a particular case of the Curcci-Ferrari (CF) model [12]. This provides a solid first-principle field theoretical justification for the phenomenological approach recently proposed in [13,14].…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…We also demonstrate that, within perturbation theory, correlation functions of YM fields are identical to those obtained in a massive extension of the usual FP gauge-fixed action, which is a particular case of the Curcci-Ferrari (CF) model [12]. This provides a solid first-principle field theoretical justification for the phenomenological approach recently proposed in [13,14].…”
Section: Introductionsupporting
confidence: 65%
“…We see that the action (16), with (13) and (21)- (23), thus describes a collection of n gauged supersymmetric nonlinear sigma models [19]. It is invariant under the super gauge transformation…”
Section: Defining Further the "Super Gauge Transform"mentioning
confidence: 99%
See 1 more Smart Citation
“…Tissier and Wschebor [8] have shown that straightforward one-loop perturbation theory applied to Yang-Mills theory with a gluon mass term yields results for the gluon and ghost propagators that reproduce surprisingly well the propagators found on the lattice in three and four space-time dimensions in the IR regime. It is apparent, however, that a renormalization group improvement is necessary for a quantitative description of the ultraviolet (UV) regime in four space-time dimensions, and also for a quantitatively good fit to the propagators in the IR regime in three dimensions.…”
mentioning
confidence: 75%
“…In the case of the coupling constant, this means that the IR fixed point is trivial. The triviality of the fixed point explains the success of straightforward perturbation theory in the IR regime (in four dimensions) [8]. On the other hand, the fact that the mass parameter tends to zero does not mean that one recovers a massless theory in the deep IR: the scale dependence of the gluon field renormalization constant leads to a finite limit of the gluon propagator at zero momentum.…”
mentioning
confidence: 99%